Cooperative vigilance: The guanaco's (Lama guanicoe) key antipredator mechanism - Taraborelli, Paula; Gregorio, Pablo; Moreno, Pablo; Novaro, Andrés; Carmanchahi, Pablo (Behavioural processes, 2012)
► Detection and flight distances from predator increased with number of guanacos per group. ► Detection and flight distances increased with distance among guanacos within the social group. ► Solitary adult males showed shorter distance moved and mixed groups greater distances moved. ► In areas with tall and dense vegetation flight distance was greater than in areas with low vegetation. ► A benefit of social grouping is an increased probability of survival with cooperative vigilance. The concept of sociality has been associated with the effectiveness of antipredator mechanisms, like cooperative vigilance and the dilution effect. Lama guanicoe (guanaco) is a social native herbivore in South America and a social species. The objectives of this study were to evaluate the antipredator responses of different-sized groups of guanacos in areas with varying predation risks and to determine antipredator mechanisms in guanacos. For this, we measured different antipredator responses to a potential predator (human subjects). Detection of predator and flight distances from predator both increased with a greater number of guanacos per group and with greater distances among guanacos within the social group. Both buffer distance and flight time decreased with a greater number of guanacos per group, but increased with greater distances among guanacos inside the social group. Solitary adult males moved shorter distance and mixed groups moved greater distances. Flight distances were greater in areas with tall and dense vegetation than in areas with low vegetation. Buffer distance and flight time were shorter in undulating land than on flat lands, and groups were usually observed on hill slopes. Our results suggest that the benefit of social grouping in guanacos is the increased probability of avoiding predator with cooperative vigilance and not with the dilution effect. This means that a predator could be detected earlier when approaching a guanaco group than when approaching a solitary individuals and could thus be avoided.